The Comprehensive Approach to EU Crisis Management: Contexts, Lessons Identified, and Policy Implications - Kammel, Arnold H.; Zyla, Benjamin (Journal of Regional Security, 2018)
Contemporary military operations take place in complex environments that are pop- ulated by multiple civilian and humanitarian actors facing an array of challenging issues that are not precisely ‘military’ in nature. This has increased the importance of addressing and managing the civil-military interface, particularly that between military and humanitarian organisations. In recognising that their relationship is not harmonious, organisations such as the EU have de- veloped a so-called ‘Comprehensive Approach’ (CA) to better align the military and civilian re- sponses to fragile states. Surprisingly, the EU’s CA has been understudied while its counterparts at NATO and the UN have received much of the attention. This article fills that gap, and shows that although the CA is clearly visible in official EU documents, the EU’s practical challenges with implementing and ‘living’ it remain immense.